Three-dimensional imaging in double aberration-corrected scanning confocal electron microscopt, Part I: elastic scattering - Cosgriff, E; D'Alfonso, A; Allen, L; Findlay, S; Kirkland, A; Nellist, P (Elsevier, 2008)
A transmission electron microscope fitted with both pre-specimen and post-specimen spherical aberration correctors enables the possibility of aberration-corrected scanning confocal electron microscopy. Imaging modes available in this configuration can make use of either elastically or inelastically scattered electrons. It is shown that there is no linear phase contrast in the confocal condition, leading to very low contrast for a single atom. Multislice simulations of a thicker crystalline sample show that sample vertical location and thickness can be accurately determined. However, buried impurity layers do not give strong, nor readily interpretable contrast. The accompanying paper examines the detection of inelastically scattered electrons in the confocal geometry.